Analysis of peak locomotor demands in professional female soccer players: An approach based on position and the day of the microcycle - Rodríguez-Fernández, A.; Oliva-Lozano, J. M.; Díaz-Seradilla, E.; Villa-Vicente, J. G.; Marroyo, J. A. R. (Journal of Science in Sport and Exercise, 2025)
Purpose The aim of this study was to examine the peak locomotor demands of match play and determine if these situations are replicated in training, and analyze their dynamics throughout the competitive microcycle in professional female soccer players based on their positions.